IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL ASSITED BY THREE TIER TEST ON CRITICAL THINKING - Sudirman Raja; Halima Imha; Muhammad Yusuf Hidayat (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2021)
The study was conducted to: determine the critical thinking skills of students before and after being taught with the guided inquiry learning model assisted by three tier test, determine the critical thinking skills of students before and after being taught by the direct instruction learning model and determine the differences in the critical thinking skills of students who are taught using the direct instruction model guided inquiry learning model assisted by three tier test with students who are taught using direct instruction learning model. This type of research is a quasi-experimental design with a nonequivalent control group design. The study was conducted at MAN Pinrang with a population all students of class XI MIPA at MAN Pinrang. The number of samples taken was 22 students in the control class (XI MIPA 1) and 22 students in the experimental class (XI MIPA 2). Hypothesis testing using a two-sample independent t-test with the results showed that the hypothesis test obtained a sign value (2-tailed) of 0,000. Because the sign value (2-tailed) < 0,05, H0 is rejected and H1 is accepted. So we can be concluded there are differences in the critical thinking skills of students who are taught using the guided inquiry learning model assisted by three tier test with those taught using the direct instruction learning model for class XI MIPA at MAN Pinrang.